The Dynamics of Islamic Science in Developing the Madrasah Diniyah Curriculum - Suparjo (Jurnal Iqra': Kajian Ilmu Pendidikan, 2023)
The article aimed to explore the dynamic of curriculum development of some madrasah diniyahs in Central Java, Indonesia. It focused on the genealogy of Islamic science and the sociocultural context of the curriculum within perspectives of education, sociology, and Islamic studies. The data were collected through semi-structured interviews and documentation techniques and applied model of Miles and Huberman model. It finally found that each survived madrasah diniyah has a specific model for developing and implementing a curriculum based on its Islamic science genealogy and sociocultural background. The curriculum was designed pragmatically and conservatively. However, it was developed adaptively to respond to sociocultural changes in society. The curriculum was designed conservatively by adopting traditional Islamic scholarship developed by most madrasah diniyyah. It was implemented pragmatically by adopting teaching materials from existing printed books, simple works of teachers, and teachers' spontaneous creativity in teaching. The curriculum was developed adaptively by responding to sociocultural changes in society. Reductions and additions were made to learning materials according to student needs, reduced study hours, and some classes were held at night. In principle, the madrasah diniyyah's curriculum provides added value and complements the learning of Islamic Religious Education in formal schools.